Forms of Potassium in Some Soils of Udaipur District - Panwar, B S; Pannu, B S; Khatri, P B (Annals of Arid Zone, 2016)
Different forms of potassium were estimated from Kumawanton-ka-guda. Dulawanton- ka-guda. Khamnor. Hunder and Negodia villages of Udaipur district of Rajasthan. Resulls revealed that water soluble potassium and exchangeable potassium ere higher while nitric acid extractable potassium and reserve potassium werc lower than the data for some other soils of Udaipur district of Rajasthan. The values of correlation coefficient among different available potassium indices were quite high. indicating the equilibrium between different forms of potassium.